1H NMR metabolomic profiling of the blue crab (Callinectes sapidus) from the Adriatic Sea (SE Italy): A comparison with warty crab (Eriphia verrucosa), and edible crab (Cancer pagurus). (1st April 2016) - Zotti, Maurizio; De Pascali, Sandra Angelica; Del Coco, Laura; Migoni, Danilo; Carrozzo, Leonardo; Mancinelli, Giorgio; Fanizzi, Francesco Paolo
Highlights: The first metabolomic study among three crab species was reported. Lipid and aqueous extracts of raw claw muscle from three crab species were analyzed. 1 H NMR spectroscopy and MVA underlined metabolic profile differences among species. Aqueous extract showed higher significance with respect to lipid fractions. Metabolomics may support the nutritive value assessment of the crustaceans seafood. Abstract: The metabolomic profile of blue crab ( Callinectes sapidus ) captured in the Acquatina lagoon (SE Italy) was compared to an autochthonous ( Eriphia verrucosa ) and to a commercial crab species ( Cancer pagurus ). Both lipid and aqueous extracts of raw claw muscle were analyzed by 1 H NMR spectroscopy and MVA (multivariate data analysis). Aqueous extracts were characterized by a higher inter-specific discriminating power compared to lipid fractions. Specifically, higher levels of glutamate, alanine and glycine characterized the aqueous extract of C. sapidus, while homarine, lactate, betaine and taurine characterized E. verrucosa and C. pagurus . On the other hand, only the signals of monounsaturated fatty acids distinguished the lipid profiles of the three crab species. These results support the commercial exploitation and the integration of the blue crab in human diet of European countries as an healthy and valuable seafood.